PENDAMPINGAN MICROTEACHING COMPUTATIONAL THINKING PADA KELOMPOK GURU MTS AL YAKIN SEBAGAI BEST PRACTICE PROSES LITERASI DIGITAL DI SEKOLAH - Sa’ida, Ita Aristia; Santi, Nirma Ceisa; Audytra, Hastie; Dirgantoro, Guruh Putro; Wulandari, Devi Ayu (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Lack of Computational Thinking in schools can cause problems including lack of problem-solving skills, limited creativity, lack of abstract thinking skills, inability to manage and analyze data, lack of understanding of the implications of technology, and lagging behind in career preparation. Therefore, it is important to strengthen the teaching of Computational Thinking in schools so that students have the skills and understanding needed to face challenges in the digital era. To overcome the problem of lack of Computational Thinking in schools, it is important to improve adequate curriculum, provide training and support to teachers, provide sufficient resources and access to technology, raise awareness of the importance of Computational Thinking, and encourage integration with other subjects. Socialization of Computational Thinking in schools can help prepare students to face an increasingly digital and complex world and can help overcome several problems related to technological developments and competency needs in the digital era. Through the socialization of Computational Thinking, problems such as lack of computational thinking skills, inability to solve complex problems, lack of understanding of the impact of technology, lack of integration of technology in learning, and less than optimal preparation for the digital workplace can be overcome. Thus, students can be better prepared to face challenges and take advantage of opportunities in the ever-evolving digital era